Enhanced Polyphenols Recovery from Grape Pomace: A Comparison of Pressurized and Atmospheric Extractions with Deep Eutectic Solvent Aqueous Mixtures - Nils Leander Huamán-Castilla; Nicolás Gajardo-Parra; José R. Pérez-Correa; Roberto I. Canales; Maximiliano Martínez-Cifuentes; Gabriela Contreras-Contreras; María Salomé Mariotti-Celis (MDPI AG, 2023)
Deep eutectic solvents (DES) are emerging as potent polyphenol extractors under normal atmospheric conditions. Yet, their effectiveness in hot pressurized liquid extraction (HPLE) must be studied more. We explored the ability of various water/DES and water/hydrogen bond donors (HBDs) mixtures in both atmospheric solid liquid extraction (ASLE) and HPLE (50%, 90 °C) for isolating specific polyphenol families from Carménère grape pomace. We assessed extraction yields based on total polyphenols, antioxidant capacity, and recovery of targeted polyphenols. The HBDs ethylene glycol and glycerol outperformed DES in atmospheric and pressurized extractions. Ethylene glycol exhibited a higher affinity for phenolic acids and flavonols, while flavanols preferred glycerol. Quantum chemical computations indicated that a high-water content in DES mixtures led to the formation of new hydrogen bonds, thereby reducing polyphenol-solvent interactions. HPLE was found to be superior to ASLE across all tested solvents. The elevated pressure in HPLE has caused significant improvement in the recovery of flavanols (17-89%), phenolic acids (17-1000%), and flavonols (81-258%). Scanning electron microscopy analysis of post-extraction residues suggested that high pressures collapse the plant matrix, thus easing polyphenol release.